Business valuation: classical and advanced methods - Saksonova, Svetlana; Abramishivi, Neli; Papiashvili, Tatiana (University of Latvia, 2020)
The topic chosen by the authors implies a qualitative rather than quantitative research approach. The aim of this paper is having assessed the value of a particular company using classical and advanced approaches to analyse the evaluation results obtained using different approaches and give recommendations to company managers. To achieve the aim, the following objectives were set: explore different views on the interpretation of the company as a subject of evaluation; analyse the major methods of assessing the value of companies; having gathered empirical data, assess the value of the particular company using classical and advanced methods; conduct a sensitivity analysis by considering factors that influence the valuation of the company. In the framework of this research, we used the key methods of assessing the value of company’s business, based both on classical approaches, such as income approach and comparative approach (market approach), and on more advanced and less studied methods, such as EVA and ROV. As a result, the possibility of using advanced methods based on economic added value and real options was demonstrated. The results obtained in the framework of various methods are comparable, and the differences indicate the need for further research in this field.
Keywords: business valuation; company’s value; EVA method; real option value; Research Subject Categories::SOCIAL SCIENCES::Business and economics